Биохимическая трансформация нефтяных углеводородов в водах Западной Сибири - Panicheva, L. P.; Moiseyenko, T, I.; Kremleva, T. A.; Volkova, S. S.; Паничева, Л. П.; Моисеенко, Т, И.; Кремлева, Т. А.; Волкова, С. С. (Издательство Тюменского государственного университета, 2012)
Study of biochemical transformation of petroleum hydrocarbons and nitrates in the waters of 127 lakes, (from the tundra to the forest-steppe zone) effect in the territory of Western Siberia (WS). The main anthropogenic sources of pollution by oil products and nitrates are the exploitation of oil and gas exploration and gas flaring. For most of the lakes in WS, quite distant from the sources of anthropogenic pollution self-purification capacity water reservoirs during the summer reduces petroleum hydrocarbons and nitrate content to below the maximum permissible concentration (MPC) for the fishery reservoirs. This significantly increases the organic carbon (Corg) and organic nitrogen (Norg). For natural zones of the WS median Corg ranges from 4.38 to 26.6 mg/dm3, Norg – from 0.17 to 1.52 mg/dm3. Biochemical transformation of petroleum products includes anaerobic process of humification and aerobic process of mineralization. In the lakes of the northern and middle latitudes of the WS (above 58o latitude) humification is 80%, mineralization – 20%, in the lakes of the southern latitudes of the WS (below 58o latitude) humification – 30%, mineralization – 70%. Anaerobic oxidation of hydrocarbons and organic remains followed by recovery of nitrate to nitrite and ammonium. Amination of the intermediate products of oxidation of organic compounds leads to increased levels of organic nitrogen and humic substances. In natural areas the range of the northern and middle latitudes (tundra, forest tundra and northern taiga, middle taiga) in the waters of lakes has a significant amount of ammonium, which determines the process of humification dominance over the process of mineralization of organic matter. In natural areas range of southern latitudes (southern taiga, foreststeppe) humification process is limited almost total depletion of ammonium. The molar ratio of carbon and nitrogen in aquatic humic substances: C: N = 23,4: 1. Проведено исследование процессов биохимической трансформации нефтяных углеводородов и нитратов в водах 127 озер (от зоны тундры до лесостепной зоны) на территории Западной Сибири (ЗС). Основными антропогенными источниками загрязнения нефтепродуктами и нитратами являются эксплуатация нефтяных и газовых месторождений и сжигание попутного газа. Для большей части озер ЗС, достаточно удаленных от источников антропогенных загрязнений, самоочищающая способность водоемов в течение летнего периода обеспечивает снижение содержания нефтепродуктов и нитратов до значений ниже ПДК для рыбохозяйственных водоемов. При этом существенно увеличивается содержание органического углерода (Сорг) и органического азота (Nорг). Для природных зон ЗС медианное значение Сорг варьирует от 4,38 до 26,6 мг/ дм3, Nорг – от 0,17 до 1,52 мг/ дм3. Биохимическая трансформация нефтепродуктов включает анаэробный процесс гумификации и аэробный процесс минерализации. В озерах северных и средних широт ЗС (выше 58о широты) гумификация составляет 80%, минерализация – 20%; в озерах южных широт ЗС (ниже 58о широты) гумификация – 30%, минерализация – 70%. Анаэробное окисление углеводородов и органических остатков сопровождается восстановлением нитратов до нитритов и аммония. Аминирование промежуточных продуктов окисления органических соединений приводит к увеличению содержания органического азота и гумусовых веществ. В природных зонах диапазона северных и средних широт (тундра, лесотундра, северная тайга, средняя тайга) в водах озер содержится значительное количество аммония, что предопределяет доминирование процесса гумификации над процессом минерализации органического вещества. В природных зонах диапазона южных широт (южная тайга, лесостепь) процесс гумификации лимитируется практически полным исчерпанием аммония. Мольное отношение углерода и азота в водных гумусовых веществах: C:N = 23,4 :1.